Substitution of Protein Source with Hatchery Waste Meal in Snakehead Fish (Channa striata) Feed - Yahya, Aslam Zulfiqar; Azhar, Fariq; Alim, Sahrul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Channa striata, commonly known as snakehead fish is a freshwater species with significant economic value. The high commercial value of this fish is attributable to the albumin content in the flesh of snakehead fish. The elevated cost of fish meal constitutes a significant challenge for fish farmers, given its role in fish feed formulations. Consequently, an alternative feed substitution that is both inexpensive and reduces the use of fish meal is required. The purpose of this study was to analyse the performance of feed formulations with the use of egg hatchery waste meal as a source of protein in snakehead fish. The research method utilised a completely randomised design (CRD), incorporating five distinct treatments and three replicates. The treatments in this study were P1 (0% hatchery waste meal/100 % fish meal), P2 (25% hatchery waste meal + 75% fish meal), P3 (50% hatchery waste meal + 50 fish meal), P4 (75% hatchery waste meal + 25% fish meal) and P5 (100% hatchery waste meal). The utilisation of hatchery waste meal as a feed substitute in snakehead fish feed has been demonstrated to exert a significant effect including absolute growth rate, EPP, SGR and FCR. However, it has been observed that this substitution does not compromise the survival rate of snakehead fish. The incorporation of 25% hatchery waste meal resulted in the optimal absolute weight growth rate and specific growth rate of snakehead fish, which were 4.32 g and 3.13%, respectively.